A hydrothermal seep on the Costa Rica margin: middle ground in a continuum of reducing ecosystems - Levin, L A; Orphan, V J; Rouse, G W; Rathburn, A E; Ussler, W; Cook, G S; Goffredi, S K; Perez, Elena M; Waren, A; Grupe, B M; Chadwick, G; Strickrott, B (Proceedings of the Royal Society B: Biological Sciences, 2012)
Upon their initial discovery, hydrothermal vents and methane seeps were considered to be related but distinct ecosystems, with different distributions, geomorphology, temperatures, geochemical properties and mostly different species. However, subsequently discovered vents and seep systems have blurred this distinction. Here, we report on a composite, hydrothermal seep ecosystem at a subducting seamount on the convergent Costa Rica margin that represents an intermediate between vent and seep ecosystems. Diffuse flow of shimmering, warm fluids with high methane concentrations supports a mixture of microbes, animal species, assemblages and trophic pathways with vent and seep affinities. Their coexistence reinforces the continuity of reducing environments and exemplifies a setting conducive to interactive evolution of vent and seep biota.
Keywords: HOV Alvin (Human Occupied Vehicle)